Design of exoskeleton-type wrist human–machine interface based on over-actuated coaxial spherical parallel mechanism. (February 2018) - Lee, Jaeyong; Song, Byung-Wook; Yang, Woosung
In this study, a wrist human–machine interface with a single internal rotation center, which is efficient in terms of performance, size, and avoidance of kinematic interference, is proposed to realize the 3-degree-of-freedom rotational motion of the human wrist. For this purpose, an over-actuated coaxial spherical parallel mechanism is applied. The over-actuated mechanism is specially considered to improve the force feedback performance and to overcome the workspace limitations caused by the singularity. From a mechanical perspective, two links are coaxially connected to the base, and this rotation axis is designed to coincide with the wrist pronation–supination, which has the largest operating range in wrist motion. A prototype was fabricated and evaluated to validate the proposed mechanism. In addition, a usable design index was proposed for the design that prevents interference with the user in the workspace while minimizing the link inertia to optimize the device. This index is optimized with the general performance indices, that is, condition index and stiffness index. It was verified through simulation that the optimized wrist human–machine interface exhibited higher performance than other similar devices. In addition, range of motion is at least 104.3% than a daily living range of motion of the human wrist, guaranteeing all ranges of motion.